Hypercoagulation screening as an innovative tool for risk assessment, early diagnosis and prognosis in cancer: the HYPERCAN study. Issue 140 (April 2016) - Falanga, Anna; Santoro, Armando; Labianca, Roberto; De Braud, Filippo; Gasparini, Giampietro; D'Alessio, Andrea; Barni, Sandro; Iacoviello, Licia; ,
ABSTRACT: The HYPERCAN is a prospective observational Italian multicentre study started in 2012, structured in two main projects (i.e. Projects A and B) that involve both healthy subjects and cancer patients. The HYPERCAN study aims to assess whether the occurrence of a hypercoagulable state may be predictive of cancer diagnosis in healthy individuals, or may be predictive of disease recurrence, clinical progression and thrombosis in cancer patients. Project A involves two different large cohorts of subjects: The first cohort (Project A-1) consists of 10, 000 healthy volunteer blood donors to be enrolled and prospectively follow-up for cancer occurrence, while the second cohort (Project A-2) consists of 25, 000 people already enrolled in the framework of the general population-based Moli-Sani study. Project B involves 4, 000 adult patients with a confirmed diagnosis of four different cancer types (both limited/resected or metastatic diseases), i.e. non-small cell-lung, gastric, colorectal, and breast cancer, to be enrolled and followed up for 5 years or death. Blood samples from all enrolled subjects are collected at baseline and then at different time intervals according to specific time schedules set up for either normal subjects, or patients with limited cancers, or patients with metastatic cancers. Samples will be analysed for a panel of hemostatic proteins, clotting activation biomarkers, thrombin generation, procoagulant microparticles, and thrombophilic polymorphisms. As of November 2015, 6, 189 healthy blood donors have been enrolled in project A-1 and 2, 532 cancer patients in project B. Clinical follow-up and biological assays are ongoing. The HYPERCAN study wants to explore in different subset of individuals, affected and non-affected by malignant disease, the relationship between coagulation and cancer. The prospective design and the involvement of a large number of individuals will definitively clarify whether alterations in circulating thrombotic markers may be predictive of cancer diagnosis in an otherwise healthy subject and/or may be prognostic of cancer outcome, or of disease progression/relapse in cancer-affected individuals. Finally, the proposed screening with relatively simple and non-high-cost laboratory tests and the use of easy-obtainable peripheral blood samples add a very relevant translational value to this study. Highlights: A correlation between hypercoagulable state and increased risk of developing a subsequent cancer in healthy subjects has been proposed Markers of hypercoagulability may be prognostic of cancer outcome Results of this study could be integrated in a prognostic model for VTE